Quantitative evaluation of apical extrusion of intracanal bacteria using rotary ProTaper, K3XF, twisted and hand K-file system: An ex vivo study - Priyanka Ghogre; Hemant Ramesh Chourasia; Manish Agarwal; M P Singh; Sandeep Gurav; Rahul Ghogre (Wolters Kluwer Medknow Publications, 2015)
Aims: The aim of this study was to evaluate the number of intracanal bacteria extruded apically during root canal preparation using rotary ProTaper, K3XF, twisted, and hand K-file system. Subjects and Methods: Seventy extracted single-rooted human mandibular premolar teeth were used. Access cavities were prepared and the teeth were mounted in glass vials. Root canals were then contaminated with a pure culture of Enterococcus faecalis (ATCC 29212) and incubated at 37°C for 24 h. The contaminated roots were divided into four experimental groups of 15 teeth each and one control group of 10 teeth. Group 1: ProTaper; Group 2: K3XF; Group 3: Twisted file; Group 4: Hand K-file; Group 5: Control group. Bacteria extruded from the apical foramen during instrumentation were collected into vials. The microbiological samples were incubated in culture media for 24 h. Colonies of bacteria were counted and the results were given as number of colony-forming units (CFU)/ml. Statistical Analysis Used: The obtained data were analyzed using the Kruskal-Wallis one-way analysis of variance and Mann-Whitney U-tests. Results: There was a significant difference between the rotary and hand instrumentation system related to the apically extruded intracanal bacteria. Conclusions: Both the rotary and hand instrumentation systems extruded intracanal bacteria through the apical foramen. K3XF file system showed least bacterial extrusion amongst all instrumentation groups.